The application of a mesoscopic scale approach in fretting fatigue - Araújo, José Alexander (2003)
This work concerns the application of a mesoscopic scale fatigue criterion to predict the initiation of cracks in components under fretting conditions. A verification of the analysis is carried out by considering available experimental data for fretting fatigue in a high strength Aluminium alloy commonly used in the aerospace industry. These experiments revealed there is a contact size effect in fretting fatigue life. The results show that the mesoscopic scale fatigue criterion can correctly predict the initiation of fretting cracks for larger contact configurations. It is concluded that the reason for the poor performance of the criterion in predicting failure at smaller contacts may well be related to the effect of the stress gradient, a variable not accounted for in the mesoscopic criterion here assessed.